Implantación de telefonía voz sobre IP utilizando la herramienta uELASTIX en un RASPBERRY PI con QoS, para la empresa ISP "KLIX DE LOJASYSTEM" de la ciudad de Loja. - Vicente Álvarez, Pablo César (2016)
This project was performed in order to implement Voice telephony over internet protocol, using μelastix software on raspberry pi with QoS for ISP "KLIX OF LOJASYSTEM" enterprise, which was configured according to the needs and business requirements of the aforementioned company. For the analysis, interpretation and requirements collection of this project, scientific methods and techniques and instruments applied to the staff of each department that uses the telephone network were used. For the implementation of the new telephone system, a raspberry pi hardware and μelastix software were used, these are considered free of charge. In order to improve the communication system, equipment that worked well with the previous software was used. The Raspberry Pi is a basic hardware, which together with the μelastix software have the necessary configurations to operate the new phone system; this software includes everything from creating phone extensions, queuing calls to the issuance of reports. As a result, the process used for the improvement of the telephone network helped the client-user synchronized communication or vice versa within the company. Tests conducted with the use of web tools allowed to obtain the results of quality of service.